Kebutuhan Angkutan Umum dan Prasarana Jalan Terhadap Perekonomian Masyarakat di Kecamatan Sebangau Kuala - Budi Sitorus; Christina Natalia Sitorus; Tulus Irpan Harsono Sitorus (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2021)
The purpose of the study is to look at the connectivity nodes that connect between Sebangau District and Pulang Pisau District and Central Kalimantan province that are still not available transportation nodes, to analyze the cost of public transportation and public transportation needs in Sebangau District, in order to improve the economy of the community. Data collection is done by collecting secondary data through literature and literature studies. Data analysis using Policy Analysis, Regression Analysis and exponential smoothing analysis. The results showed that the cost of transportation to the District Sebangau Kuala reached between Rp.191.100.00 to Rp. 443.100.00, to improve transportation connectivity required financing of Rp.125.590.893.550,-, Within a period of 10 years. The relationship between the number of Transportation, road increase with the number of APBD receipts shows a significance value of 33%.